Структура и свойства спеченных материалов на основе системы Fe-Cu-C, полученных с применением различных способов легирования - Внуков, Александр Александрович (НТУ "ХПИ", 2015)
Рассмотрены основные способы легирования порошковых конструкционных сталей. Исследован комплекс физических и механических свойств спеченных конструкционных материалов на основе железа, полученных с применением различных технологических приемов легирования медью и углеродом: механического смешивания, механосинтеза и омеднения. Проведен сравнительный анализ свойств полученных материалов и определен оптимальный способ легирования. Результаты исследований могут быть использованы при создании спеченных сталей и сплавов с повышенными эксплуатационными свойствами.

Currently, there is the need for broader implementation in production of powder alloy steels. In the literature there are publications on the properties of these materials, methods of alloying. However, their fragmentation makes it difficult to use these data to develop new powder alloy steels, and their introduction into production. In this connection it is appropriate to conduct studies on the effect of alloying methods on the properties of powder steels. The main methods of obtaining powder alloyed steels are the preparation of multicomponent mixtures of powders of iron and alloying elements; the use of iron alloy powders; impregnation liquid alloy metal or diffusion saturation skeletons of sintered iron powders. Considered the main methods of powder constructional steels alloying. Investigated the complex of physical and mechanical properties of the sintered structural materials based on iron obtained using different technological methods of alloying copper and carbon: the mechanical mixing mechanosynthesis and copper plating. A comparative analysis of the properties of the materials and determine the best way of alloying. The research results can be used to make sintered steels and alloys with high performance properties.
The structure and properties of sintered materials based on the system Fe-Cu-C, obtained using different methods of alloying
Keywords: методы порошковой металлургии; механическое смешивание; механосинтез; омеднение; спеченные стали; sintered steel; mechanosynthesis; copper plating; iron powder; copper powder